Human Papilloma Virus in Cervical Cancer Carcinogenesis and Its Immunology - Hussain, Maleeha (Bangladesh Journal of Pathology, 2011)
DOI: http://dx.doi.org/10.3329/bjpath.v26i1.9125 BJPATH 2011; 26(1): 1-2